DESIGN OF MACHINE LEARNING DETECTION MASK USING YOLO AND DARKNET ON NVIDIA JETSON NANO - Deny Danu Prasetia; Andrie Yuswanto; Budi Wibowo (TEKNOKOM, 2022)
In the Covid-19 pandemic, wearing a mask has become the obligation of Indonesian citizen,for outdoor and indoor.  Public awareness of wearing masks when leaving the house according to the government's appeal is still low.  This can be seen from the many people who do not wear masks while on the public place or in other place.  Technology that can help increase public awareness of using masks is a mask detection application.  The application to detect use of masks is made using Artificial Intelligence and uses machine learning methods from a tool that will read every use of masks on the face automatically, either using masks appropriately, using inappropriate masks or not using masks. The method used in this research is to use the Research and Development method, namely research that can produce a product. Based on the test results using masks with facial motifs, there are different results from the two samples tested depending on the quality of the image on the mask Yolo (You Only Look Once) is an object detection system in real time.  Darknet is an open source neural network framework written in the C and CUDA programming languages.  The Jetson Nano is a System On Module (SoM) and developer kit from the Nvidia Jetson family.